Equity and Inclusion in Education: Finding Strength through Diversity - OCDE (Organisation for Economic Co-operation and Development, 2023)
Governments and education policy makers are increasingly concerned with equity and inclusion in education due to several major global trends such as demographic shifts, migration and refugee crises, rising inequalities, and climate change. These...